Revitalizing Mosque Management: A Social and Cultural Framework for Boosting Local Economic Growth - Mhd. Indra Mulia Nasution; Mustapa Khamal Rokan; Muhammad Habibi Siregar (Jurnal Ilmiah Manajemen Kesatuan, 2025)
Mosques have strategic potential not only as places of worship but also as centres for community economic empowerment. This study aims to analyze the potential, solutions, and strategies for strengthening mosque management in supporting the economic empowerment of surrounding communities through social and cultural approaches. The method used is the Analytic Network Process (ANP), which integrates both qualitative and quantitative approaches, including in-depth interviews, participatory observations, and questionnaires involving religious leaders, cultural experts, mosque administrators, and local business actors. The findings show that the social approach is effective in building trust and community participation, with programs such as charity distribution, healthcare services, economic training, and guidance for converts strengthening solidarity and self-reliance. The cultural approach plays a crucial role in enhancing community identity and acceptance of the mosque. The acculturation of local culture with Islamic values increases the mosque’s relevance in daily life. A successful mosque management model involves visionary leadership, financial transparency, and productive community activities such as cooperatives and MSME bazaars. This study contributes to mosque management by integrating social and cultural approaches through ANP and provides strategic guidance for mosque managers to optimize the mosque’s social, cultural, and economic functions to improve public welfare.